The Impact Of Dating On Mental Health In Adolescents - Yunda Fithriyah (Academic Journal of Psychology and Counseling, 2022)
Adolescents still do not realize that many Islamic teachings are established to protect their well-being and mental health. Dating, which is forbidden in Islam, has become more common among adolescents in recent days. Adolescents use love as the main reason for dating. This article aimed to examine the impact of dating on adolescents’ mental health. This study used a qualitative method with a phenomenological approach. Data was collected through observation and interviews with ten informants aged 19 to 22 (five informants had dated and the others did not). The study found that adolescents who have romantic relationships before marriage have greater stress levels than those who stay single. Prohibiting romantic relationships outside marriage is considered a form of Islamic teaching that safeguards human well-being.